In vivo antidiabetic efficacy of Malaysian Vernonia amygdalina aqueous extract - Zakaria, Yusmazura; Zainul Azlan, Nurhazirah; Nik Hassan, Nik Fakhuruddin; Muhammad, Hussin (AkiNik Publications, 2018)
Diabetes mellitus (DM) is a major world health concern especially DM types 2. In Malaysia, about 2.6 million adults were diagnosed with diabetes and most of them turn to herbal medicine for treatment. Vernonia amygdalina or locally known as bitter leaf is believed by the local people and traditional inhaler to reduce blood glucose level. This study aims to prove the antidiabetic property of Malaysian local V. amygdalina as claim by the local Malaysian. V. amygdalina aqueous extract was prepared by reflux method and was further concentrated. Twenty male Sprague Dawley rats were divided into 4 groups; non-diabetic rats as normal control (NC), diabetic induced rats as diabetic control (DC), diabetic induced rats treated with 150 mg/kg metformin and diabetic induced rats treated with 50 mg/kg V. amygdalina aqueous extract. The diabetic rats were induced by using 40 mg/kg of Streptozotocin (STZ). The study was conducted for 28 days. Body weights (BW) were taken at weekly interval for 4 weeks. Fasting blood glucose was measured in 3 day intervals. At the end of experiment, blood samples were collected for lipid profile test and insulin secretion assay. There were no significant differences in BW, relative organ weight (ROW) and no organs abnormalities were observed in all experimental groups. Significant decreases in triglycerides, total cholesterol and fasting blood glucose gave a prove evidence that V. amygdalina possessing antidiabetic property. However, the levels of insulin in diabetic induced rats treated with V. amygdalina aqueous extract were not significant as compared to the diabetic induced rats treated with metformin. The aqueous extract of V. amygdalina has antidiabetic activity. This work supports the folk use of this plant in treating diabetes. This antidiabetic property of Malaysian V. amygdalina may due to its phytochemical constituents as our previous study revealed the high contents of flavonoids and terpenoids. However, the aqueous extract of V. amygdalina did not act through regulation of insulin hormone since there was no significant change in insulin level.